Implementasi Akuntansi Lingkungan pada Industri Pabrik - Luga, Lusia Rechylia; Renggo, Febriani Santika; Mayanes, Angelita; Pare, Klemensia (EDUPEDIA Publisher, 2023)
Implementation of the Implementation of Environmental Accounting related to waste processing costs at Mr. Budi Nuryanto's tofu factory as a form of responsibility for community service. In carrying out their business activities, there is a problem faced by business actors, namely not understanding the importance of implementing environmental accounting for business continuity, especially related to the costs of processing factory waste. The aim of this community service activity is to help business actors understand the importance of implementing environmental accounting in tofu factories, especially regarding waste processing costs. The method used in PKM is Skill Training or skills training which is training that is often found in various organizations.Based on the results obtained from the activities, business actors realize how important it is to implement environmental accounting regarding waste processing costs which can also be used as income. This can be seen in the presentation of waste processing costs. Keywords: Environmental Accounting, waste processing costs